2012
DOI: 10.3905/jod.2012.19.3.029
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Trading Activity on theSingle-Stock Futures Market: Evidence from theEurex Exchange

Abstract: Notes: The top panel plots the average mispricing abnormal volatility around 990 ex-dividend dates for 420 companies. The sharp decrease of mispricing indicates improvement in market efficiency. The lower panel depicts the average level of the open interest and the traded volume around ex-dividend dates. The left-hand scale corresponds to the traded volume and the right-hand one to open interest. The scales are different. Both magnitudes tend to increase, revealing the high market activity around the event dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In the literature, two main aspects have been studied when analyzing the determinants of successful contracts -definition of success and factors contributing to contract success. The prior work reviewed encompasses studies offering explanations for why a few traded contracts achieve the liquidity, requisite for success and some experience low liquidity and failure in general and some studies specifically in the context of agricultural commodities (Bialkowski and Jakubowski, 2012;Till, 2014;Webb, 2015;Garcia et al, 2015). It helps us to identify broad characteristics essential to the success of the contract and specifically examine them in the context of agricultural commodities in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, two main aspects have been studied when analyzing the determinants of successful contracts -definition of success and factors contributing to contract success. The prior work reviewed encompasses studies offering explanations for why a few traded contracts achieve the liquidity, requisite for success and some experience low liquidity and failure in general and some studies specifically in the context of agricultural commodities (Bialkowski and Jakubowski, 2012;Till, 2014;Webb, 2015;Garcia et al, 2015). It helps us to identify broad characteristics essential to the success of the contract and specifically examine them in the context of agricultural commodities in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike our earlier analysis, we can control for the other factors that might affect traded volume in this model. To control for the high correlation in traded volume between the spot market and the futures market, we use spot market traded volume as a control variable (Białkowski & Jakubowski, 2012). For our panel data estimation, we consider our period of analysis from June 13, 2015 (1 month before SEBI's announcement of minimum contract size revision) to December 31, 2015.…”
Section: Traded Volumementioning
confidence: 99%
“…σ Spot _ is the spot market volatility using Andersen et al (2001)'s definition. To control for the high correlation in traded volume between the spot market and the futures market, we use spot market traded volume as a control variable (Białkowski & Jakubowski, 2012).…”
Section: Traded Volumementioning
confidence: 99%
“…There is also a study in Taiwan by Songyoo (2012); it shows a bilateral interaction in the long run, and the futures market leads the spot market in the short run. Moreover, some studies involve the determinant of the SSF trading volume; for example, Bialkowski and Jakubowski (2012) have shown that institutional holdings, volatility, and trading volume of the underlying stocks in the spot market are the significant factor to the trading activities on SSF using the data from the Eurex Exchange.…”
Section: Single Stock Futuresmentioning
confidence: 99%